ОБ ОДНОМ СВОЙСТВЕ МНОЖЕСТВА ПЕРИОДИЧЕСКИХ РЕШЕНИЙ ДИФФЕРЕНЦИАЛЬНЫХ УРАВНЕНИЙ ВТОРОГО ПОРЯДКА С ИМПУЛЬСНЫМ ВОЗДЕЙСТВИЕМ - Елгондиев, К.К.; Казакбаева, К.Б. (SCIENCE and SOCIETY, 2021)
The problem of the properties of the solution of linear differential equations of the second order with impulsive action at fixed times is considered. The solutions of the problem are the conditions that make up the class of -parametric solutions. Начало формы
Keywords: differential equation; impulse actions; characteristic roots; periodic solutions; sets of periodic solutions